2019
DOI: 10.1140/epja/i2019-12705-7
|View full text |Cite
|
Sign up to set email alerts
|

One particle distribution function and shear viscosity in magnetic field: A relaxation time approach

Abstract: We calculate the δf correction to the one particle distribution function in presence of magnetic field and non-zero shear viscosity within the relaxation time approximation. The δf correction is found to be electric charge dependent. Subsequently, we also calculate one longitudinal and four transverse shear viscous coefficients as a function of dimensionless Hall parameter χH in presence of the magnetic field. We find that a proper linear combination of the shear viscous coefficients calculated in this work sc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 54 publications
1
33
0
Order By: Relevance
“…( 36) and ( 37) for Scalar and Dirac particle respectively. Relaxation time approximation (RTA) of kinetic theory provide the form of conductivity in terms of relaxation time as [12,17,35,37] Scalar,Dirac =…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…( 36) and ( 37) for Scalar and Dirac particle respectively. Relaxation time approximation (RTA) of kinetic theory provide the form of conductivity in terms of relaxation time as [12,17,35,37] Scalar,Dirac =…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…Thus the different components of conductivity are obtained by application of the corresponding projectors on the conductivity tensor . In RTA [12,17], it is found that electrical conductivity breaks up into multiple components with respect to the direction of the external magnetic field. In our Kubo formalism, the different components of conductivities are obtain from…”
Section: Electrical Conductivity From Spectral Function In Kubo Forma...mentioning
confidence: 99%
See 1 more Smart Citation
“…Given one uses the same basis as ref. [1], we get the following relations between the transport coefficients [82]:…”
Section: Jhep03(2021)216mentioning
confidence: 99%
“…Moreover, λ and ξ are the effective temperature and anisotropy parameters, that are, in contrast to λ 0 and ξ 0 from previous section, affected by the dissipation of the fluid. To determine δ f d , we follow the method that has been used in [9]. We use rank-two tensors…”
Section: Pos(confinement2018)259mentioning
confidence: 99%